ASSESSMENT OF VACCINE COLD CHAIN EQUIPMENT AND THEIR MANAGEMENT IN GOVERNMENT HEALTHCARE FACILITIES IN DISTRICT THARPARKAR.: J Peop Univ Med Health Sci. 2025:15(3), 144-154. http://doi.org/10.46536/jpumhs/2025/15.03.670 - Muneer Akhter Alias Waseem1, Fozia Jamal2, Rai Chand3, Muhammad Sarwar Khan4, Kenjher5, Aamir Ramzan6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Vaccination programs are essential for controlling infectious diseases, and their effectiveness relies heavily on maintaining vaccine potency through proper storage and handling. The vaccine cold chain system—comprising temperature-controlled environments for storage, management, and transportation—is critical for ensuring vaccine efficacy. OBJECTIVE: Any lapse in cold chain maintenance can lead to vaccine degradation, reducing effectiveness and posing serious public health risks. METHODOLOGY: This descriptive cross-sectional study was conducted in Tharparkar District, targeting government healthcare facilities providing vaccination services. Out of 189 total facilities, 21 were randomly selected using Open Epi software, with inclusion based on accessibility and consent. Participants from these facilities were selected through convenient sampling. Data were collected using a structured, written questionnaire covering knowledge, perceptions, and practices regarding cold chain and vaccine management. RESULTS: The findings revealed that all participants (100%) were aware of the recommended vaccine storage temperature. However, only 57% correctly performed the shake test, and 85% accurately interpreted Vaccine Vial Monitors (VVMs). Improper vaccine storage arrangements were observed in 52% of facilities. Additionally, only 43% of the facilities kept daily temperature records, and just 33% maintained accurate logs. Encouragingly, 81% of handlers adhered to the four-week open vial policy. CONCLUSION: The study highlights significant shortcomings in cold chain management practices across healthcare facilities in Tharparkar. Deficiencies in temperature monitoring, storage arrangements, and documentation practices threaten vaccine potency and compromise immunization efforts. Addressing these gaps through enhanced training, systematic monitoring, and resource provision is crucial to safeguard public health and ensure effective vaccine delivery.